2013
DOI: 10.1158/2326-6066.cir-13-0049
|View full text |Cite
|
Sign up to set email alerts
|

Human Regulatory T Cells Kill Tumor Cells through Granzyme-Dependent Cytotoxicity upon Retargeting with a Bispecific Antibody

Abstract: A major mechanism by which human regulatory T cells (Tregs) have been shown to suppress and kill autologous immune cells is through the granzyme-perforin pathway. However, it is unknown whether Tregs also possess the capacity to kill tumor cells using similar mechanisms. Bispecific antibodies (bscAbs) have emerged as a promising class of therapeutics that activate T cells against tumor antigens without the need for classical MHC-restricted TCR recognition. Here, we show that a bscAb targeting the tumor-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 23 publications
1
52
1
1
Order By: Relevance
“…They reported an efficient elimination of target antigen-expressing glioblastoma cells by anti-CD3-anti-EGFRvIII bsAbredirected Tregs. 5,6 There are several potential technical explanations for the observed differences between Choi's and our results. First, we used sorted CD4 C CD25 C CD127 low CD45RA C Tregs as starting population as it is well known that these cells have the highest capacity to maintain phenotypic and functional Treg properties after prolonged in vitro cultivation.…”
contrasting
confidence: 66%
“…They reported an efficient elimination of target antigen-expressing glioblastoma cells by anti-CD3-anti-EGFRvIII bsAbredirected Tregs. 5,6 There are several potential technical explanations for the observed differences between Choi's and our results. First, we used sorted CD4 C CD25 C CD127 low CD45RA C Tregs as starting population as it is well known that these cells have the highest capacity to maintain phenotypic and functional Treg properties after prolonged in vitro cultivation.…”
contrasting
confidence: 66%
“…These results provide indirect evidence that the Foxp3 + Eomes + CD4 + T cells may not mediate immunosuppressive effects on conventional T cells and are therefore distinct from the Treg population described by Loebbermann et al (39). It has recently been shown that granzyme B-producing Tregs can kill tumor target cells (40). However, these cells were redirected by bispecific Abs and classical TCR involvement in specific tumor cell recognition was absent.…”
Section: Discussionmentioning
confidence: 56%
“…В пользу этого предпо-ложения свидетельствуют данные ряда авторов об оппозитном эффекте IL-4 и IFNα на экспрес-сию перфорина и гранзима Б. Так, IL-4 являет-ся негативным регулятором экспрессии генов гранзима Б и перфорина в IL2-активированных NK-клетках [10]. Кроме того, IL-4 дозозависи-мо подавляет экспрессию и продукцию гранзи-ма Б в регуляторных Т-клетках (Treg), а также гранзим Б-опосредованную противоопухолевую цитотоксичность Treg [9]. В отношении IFNα, наоборот, показано стимулирующее влияние на экспрессию гранзима Б на уровне гена и са-мого белка в NK-клетках и их цитотоксическую активность [27], а также на экспрессию мРНК перфорина [20].…”
Section: Discussionunclassified